10 μm‐Thick High‐Strength Solid Polymer Electrolytes with Excellent Interface Compatibility for Flexible All‐Solid‐State Lithium‐Metal Batteries. Issue 25 (16th May 2021) - Wang, Zhiyan; Shen, Lin; Deng, Shungui; Cui, Ping; Yao, Xiayin
Abstract: An ultrathin solid polymer electrolyte (SPE) consisting of modified polyethylene (PE) as the host and poly(ethylene glycol) methyl ether acrylate and lithium salts as fillers is presented. The porous poly(methyl methacrylate)–polystyrene interface layers closely attached on both sides of the PE effectively improve the interface compatibility among electrolytes and electrodes. The resultant 10 μm‐thick SPEs possess an ultrahigh ionic conductance of 34.84 mS at room temperature and excellent mechanical properties of 103.0 MPa with elongation up to 142.3%. The Li//Li symmetric cell employing an optimized solid electrolyte can stably cycle more than 1500 h at 60 °C. Moreover, the LiFePO4 //Li pouch cell can stably cycle over 1000 cycles at 1 C rate and with a capacity retention of 76.4% from 148.9 to 113.7 mAh g −1 at 60 °C. The LiCoO2 //Li pouch cell can stably operate at 0.1 and 0.2 C rate for each 100 cycles. Furthermore, the LiFePO4 //Li pouch cell can work stably after curling and folding, which proves its excellent flexibility and safety simultaneously. This work offers a promising strategy to realize ultrathinness, excellent compatibility, high strength, as well as safe solid electrolytes for all‐solid‐state lithium‐metal batteries. Abstract : 10 μm‐thick high‐strength solid polymer electrolytes with an ultrahigh room‐temperature ionic conductance of 34.84 mS are presented. They possess excellent interfacial stability with the lithium anode. The derived flexible all‐solid‐state lithium‐metal batteries, employing LiFePO4 or LiCoO2 as cathode materials, exhibit excellent cycling stability as well as high rate capability.